Wide application of a novel topoisomerase I inhibitor-based drug conjugation technology. Issue 20 (15th October 2016) - Ogitani, Yusuke; Abe, Yuki; Iguchi, Takuma; Yamaguchi, Junko; Terauchi, Tomoko; Kitamura, Michiko; Goto, Koichi; Goto, Mayumi; Oitate, Masataka; Yukinaga, Hideo; Yabe, Yoshiyuki; Nakada, Takashi; et al.
Graphical abstract: Abstract: To establish a novel and widely applicable payload-linker technology for antibody–drug conjugates (ADCs), we have focused our research on applying exatecan mesylate (DX-8951f), a potent topoisomerase I inhibitor, which exhibits extensive antitumor activity as well as significant myelotoxicity, as the payload part. Through this study, we discovered a promising exatecan derivative (DX-8951 derivative, DXd), that has the characteristics of low membrane permeability and shows considerably less myelotoxicity than that shown by exatecan mesylate in an in vitro human colony forming unit-granulocyte macrophage assay. DXd was further used for drug conjugation by using commercially or clinically useful monoclonal antibodies to evaluate the potency of the ADC. The result revealed that the DXd-ADCs targeting CD30, CD33, and CD70 were effective against each of their respective target-expressing tumor cell lines. Moreover, a novel DXd-ADC targeting B7-H3, which is a new target for ADCs, also showed potent antitumor efficacy both in vitro and in vivo. In conclusion, this study showed that this novel topoisomerase I inhibitor-based ADC technology is widely applicable to a diverse number of antibodies and is expected to mitigate myelotoxicity, thereby possibly resulting in better safety profiles than that of existing ADC technologies.